PERBEDAAN ARUS PUNCAK EKSPIRASI ANTARA ANAK ASMA DENGAN OBESITAS DAN ANAK ASMA TANPA OBESITAS - , Nurul Hadi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background. Obesity in children is associated with impairment of pulmonary function and increased risk of asthma. Obesity in asthmatic children may reduce lung function, that can be assessed by peak flow meter, a practical and an inexpensive tool. Objectives. To compare the peak expiratory flow (PEF) between obese and non obese asthmatic children. Methods. We conducted a cross sectional study in Yogyakarta during March 2010 to September 2012. Fifty obese asthmatic patients and 50 non obese asthmatic control subjects participated in this study. Inclusion criteria were asthmatic patient, according to PNAA, 6-18 years of age. Exclusion criteria were asthmatic attack, respiratory disease, heart disease and congenital chest malformation. Obesity is defined as body mass index (BMI) for age more than +3 standard deviation (SD) WHO growth chart standards BMI for age 2007 z-score. Z-score is calculated with WHO AnthroPlus for Personal Computers. Data PEF is taken with electrical Peak Flow Meter when the patient was not suffering from asthma attack. Normal PEF was defined as PEF more than 80% average (predicted) value for height (Polgar and Promadht, 1979). Result. We recruited 50 obese children with asthma and 50 non-obese asthmatic children. The mean of age of asthmatic children in this study was 9.38 years and 9.50 years for non obese and obese respectively. There was no significant defference of the prevalence of obesity in asthmatic children who consumed medication routinely than asthmatic children without medication (P=0.16). The duration of have asthma in obese patient was not defference than non obese patient (P=0.06). There were no differences of PFR in term of gender, consume medication and smoker in the family patient with asthma. The PFR was not different between obese asthmatic children and non obese asthmatic children (P=0,83). Pearson correlation about PFR and z-score BMI for age was positive weak correlation (r=0.12). There was significant difference of PFR between z-score BMI for age <3,20 and z-score BMI for age â¥3.20 (P=0.03). Significant difference of PFR was also appear in duration of illness (P<0.001). Conclusion. There is no difference PFR between obese asthmatic children and nonobese asthmatic children. The difference of PFR emerges when statistic analysis using z-score BMI â¥ 3.20.